Advanced image processing techniques and applications - Kumar, N. Suresh, 1979-; Sangaiah, Arun Kumar, 1981-; Arun, M., 1979-; Anand, S. (Engineer) (IGI Global, 2017)
"This book is an essential reference publication for the latest research on digital image processing advancements. Featuring expansive coverage on a broad range of topics and perspectives, such as image and video steganography, pattern recognition, and artificial vision"-- Provided by publisher.
"Premier reference source"-- book cover.
Keywords: Image processing -- Industrial applications -- Handbooks, manuals, etc.; Image processing -- Digital techniques.; elektronické knihy; electronic books